Can Bilateral Investment Treaties Boost Foreign Direct Investment? An Analysis of State Competition for Capital - Hassas, Mawloda; Mohammadi, Rezwana; Amany, Marefat (Business and Human Rights Law & Policy, 2026)
This study seeks to answer whether Bilateral Investment Treaties (BITs) genuinely help boost Foreign Direct Investment (FDI) inflows amid growing international competition for capital. While BITs are widely used to mitigate political and regulatory risks and offer investor-state dispute mechanisms, their actual impact on attracting FDI remains contested. This paper evaluates which BITs enhance FDI and under what specific circumstances they are effective. Employing a qualitative research method and doctrinal legal analysis, as well as comparison of Vietnam and Afghanistan. The paper draws on Rational Choice Institutionalism and International Political Economy to explain state and investor behaviour. The results indicate that although BITs may increase investor confidence by signalling protection, they are insufficient on their own for attracting FDI. Their effectiveness depends largely on domestic institutional quality, political stability, and supportive economic policies. The study recommends integrating BITs into a broader investment policy rather than relying on them in isolation.